2014
DOI: 10.3109/11038128.2014.952333
|View full text |Cite
|
Sign up to set email alerts
|

A process for developing sustainable evidence-based occupational therapy practice

Abstract: The findings showed how an occupational therapy model of practice, such as the OTIPM, can guide an improvement process and keep it going over a long period of time, thereby supporting sustainable improvements in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The participant who said “I'd like to say that I don't have time, but actually if I wanted to make the time I could” reflects something of a dilemma in that the therapist shows a sense of awareness about something lacking in her practice and yet chooses not to prioritize what she considers best practice. Based upon the findings in this study, this phenomenon or trend is something that occupational therapists need to look more carefully at in order to improve possibilities for changing practices and for further work in the integration of research and clinical practice [ 6 , 32 ]. Although being beyond the scope of this paper, it can also be of interest for occupational therapists to look at implementation science as a way to facilitate the integration of best practices [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participant who said “I'd like to say that I don't have time, but actually if I wanted to make the time I could” reflects something of a dilemma in that the therapist shows a sense of awareness about something lacking in her practice and yet chooses not to prioritize what she considers best practice. Based upon the findings in this study, this phenomenon or trend is something that occupational therapists need to look more carefully at in order to improve possibilities for changing practices and for further work in the integration of research and clinical practice [ 6 , 32 ]. Although being beyond the scope of this paper, it can also be of interest for occupational therapists to look at implementation science as a way to facilitate the integration of best practices [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in northern Sweden, occupational therapists working in an acute hospital facility were interviewed regarding their experiences with integrating client-centeredness and occupation-focus into their practice based on the use of the Occupational Therapy Intervention and Process Model (OTIPM) [ 6 ]. Unsurprisingly, occupational therapists experienced a transformation of thought and action as they explicitly worked with a model to critically reflect on their own practices.…”
Section: Introductionmentioning
confidence: 99%
“…The Occupational Therapy Intervention Process Model (OTIPM) was used as theoretical framework for the development of the AT intervention (Fisher, 2009). The model was chosen because the OTIPM has been used previously within the field of AT (Kassberg and Skär, 2008;Linden et al, 2010), and because studies have shown that the model can be used to guide an improvement process and lead to an integration of evidence-based knowledge in practice, with long-lasting achievements (Sirkka et al, 2014a(Sirkka et al, , 2014b. In line with the OTIPM, the AT intervention entails the following three phases: evaluation and goal setting, intervention, and re-evaluation.…”
Section: An Evidence-based Client-centered At Interventionmentioning
confidence: 99%
“…Active involvement in research and partnerships between practitioners and universities are recognized as facilitators of EBP. Additionally, literature suggests the presence of several factors such as appropriate workload, support from the clinical team and disciplinary manager, and even the availability of sufficient evidence in the discipline as the key elements required to consolidate EBP (Bennett et al, 2003;Copley & Allen, 2009;Humphris et al, 2000;Sirkka et al, 2014). Without these additional factors, scientific findings may not be ably integrated into daily occupational therapy practice (Cameron et al, 2005;Thomas & Law, 2013).…”
Section: Sources Of Information Used In Evidence-based Occupational Tmentioning
confidence: 99%